Benzoylaconine: Potential Therapeutic Agent for Cardiovascular Diseases From Fuzi - Chenggang Xu; Le Tang; Lixin Hu; Yunzhe Huang; Jin Tang; Xiaohu Wang; Feng Wang (Cardiovascular Therapeutics)
Modern pharmacological studies have elucidated the presence of aconitine (AC) alkaloids, polysaccharides, and saponins as the primary bioactive constituents of Fuzi. Among these, benzoylaconine, a pivotal active compound, demonstrates notable pharmacological properties including antitumor, anti-inflammatory, and cardiovascular protective effects. In recent years, benzoylaconine has garnered significant attention in basic research on heart diseases, emerging as a focal point of investigation. This paper presents a comprehensive review of the pharmacological effects of benzoylaconine, alongside an overview of advancements in metabolic characterization. The objective is to furnish valuable insights that can serve as a cornerstone for further exploration, utilization, and advancement of benzoylaconine in pharmacological research.